The complete mitochondrial genomes of two skipper genera (Lepidoptera: Hesperiidae) and their associated phylogenetic analysis. Issue 1 (December 2018) - Han, Yuke; Huang, Zhenfu; Tang, Jing; Chiba, Hideyuki; Fan, Xiaoling
Abstract The systematic positions of two hesperiid genera, Apostictopterus andBarca (Lepidoptera: Hesperiidae), remain ambiguous. We sequenced and annotated the two mitogenomes ofApostictopterus fuliginosus andBarca bicolor and inferred the phylogenetic positions of the two genera within the Hesperiidae based on the available mitogenomes. The lengths of the two circular mitogenomes ofA. fuliginosus andB. bicolor are 15, 417 and 15, 574 base pairs (bp), respectively. These two mitogenomes show similar AT skew, GC skew, codon usage and nucleotide bias of AT: the GC skew of the two species is negative, and the AT skew ofA. fuliginosus is negative, while the AT skew ofB. bicolor is slightly positive. The largest intergenic spacer is located at the same position betweentrnQ andND2 inA. fuliginosus (73 bp) andB. bicolor (72 bp). Thirteen protein-coding genes (PCGs) start with ATN codons except forCOI, which starts with CGA. The control regions of both mitogenomes possess a long tandem repeat, which is 30 bp long inA. fuliginosus, and 18 bp inB. bicolor . Bayesian inference and maximum likelihood methods were employed to infer the phylogenetic relationships, which suggested thatA. fuliginosus andB. bicolor belong in the subfamily Hesperiinae.